Blood Biochemical Dynamics and Correlations in Laying Hens after Experimental Nickel Administration - Capcarova, Marcela; Kolesarova, A.; Arpasova, H.; Massanyi, P.; Lukac, N.; Kovacik, J.; Kalafova, A.; Schneidgenova, M. (International Journal of Poultry Science, 2008)
The concentrations of biochemical parameters (calcium, phosphorus, magnesium, sodium, potassium, glucose, total cholesterol, total proteins, triglycerides, alanine aminotransferase ALT, aspartate aminotransferase AST, gamma glutamyl transferase GGT and glutamatdehydrogenase GLDH) and their correlations in blood serum of Isa brown breed of laying hens after nickel administration were analyzed. Animals were divided into four groups (K, P1, P2, P3). Experimental hens (5 in each group) received nickel (NiCl2) per os in drinking water in various dose (P1 - 20 mg NiCl2/L; P2 - 200 mg NiCl2/L; P3 - 2000 mg NiCl2/L of drinking water) for 28 days, control group - K (n=5) did not receive nickel during experiment. Blood collection was realized at Day 0 (collection - control), Day 7 (collection 1), Day 14 (collection 2), Day 21 (collection 3) and Day 28 (collection 4). Significant decreases (P